PENGEMBANGAN WISATA PANTAI MJ ARUNG PARAK SEBAGAI OBJEK WISATA DI KECAMATAN TANGARAN KABUPATEN SAMBAS - Syukur Abidin; Sri Buwono; Nur Meily Adlika (Universitas Tanjungpura, 2021)
AbstractThis study aims to analyze the potential of MJ Beach as a tourist attraction. Type of research used descriptive with qualitative methods. Data retrieval procedure in this study is observation, interview and documentation. Results of the research obtained in this study is the result of an interview that is a description of the tour-ism potential of MJ Beach. Based on the results of the research, Arung Parak vil-lage has two tourism potentials, namely MJ Beach and Antar Ajong festival. MJ Beach has the advantage of having two tourism potentials as well as good acces-sibility. The weakness of MJ Beach is the lack of tourist support facilities and coastal abrasion. The opportunity that MJ Arung Parak Beach has is the presence of Pokdarwis and the trend of people who choose to travel in their own area. The threat in the development of MJ is the presence of other beaches that are more in demand by the community as well as the effects of Covid-19. The direc-tion of development that can be done is to utilize with both tourism potentials that have to be used as tourist attractions, misinterpret the condition of existing facili-ties, and still maintain the sustainability of the beach.Keywords: Tourism development, tourist attraction, beach